2020
DOI: 10.1016/j.cmi.2019.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Association between type-specific influenza circulation and incidence of severe laboratory-confirmed cases; which subtype is the most virulent?

Abstract: Objectives: Excess population mortality during winter is most often associated with influenza A(H3N2), though susceptibility differs by age. We examined differences between influenza types/subtypes in their association with severe laboratory-confirmed cases, overall and by age group, to determine which type is the most virulent. Methods: We used nine seasons of comprehensive nationwide surveillance data from Greece (2010 e2011 to 2018e2019) to examine the association, separately for influenza A(H1N1)pdm09, A(H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…It has been reported that A(H3N2) particularly affected elderly people, as was found herein, leading to a high mortality and ICU admission rates in this population [9]. Although considered as less severe and mainly responsible for mild presentation in children, B infections can also cause severe and fatal cases [14], notably due to the development of bacterial co-infections [15].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…It has been reported that A(H3N2) particularly affected elderly people, as was found herein, leading to a high mortality and ICU admission rates in this population [9]. Although considered as less severe and mainly responsible for mild presentation in children, B infections can also cause severe and fatal cases [14], notably due to the development of bacterial co-infections [15].…”
Section: Discussionsupporting
confidence: 66%
“…Since 2009, A(H1N1)pdm09 has also been reported to be the most frequently detected in ICU patients, underscoring the particular virulence of this influenza subtype [4,8,9]. T€ opfer et al found that A(H1N1)pdm09-ARDS led to a more important impairment of gas exchange than non-A(H1N1)pdm09-ARDS; interestingly, the rate of bacterial co-infection between the two groups was not different [10].…”
Section: Discussionmentioning
confidence: 99%
“…The reasons behind this interesting finding are still unclear. We observed that patients with influenza A (H1N1) were more likely to require ICU support than those with either influenza A (H3N2) or influenza B 59‐61 . Therefore, it is plausible that influenza A (H1N1) may reflect more severe illness, which could partly explain the higher risk of IPA in this influenza subtype population.…”
Section: Discussionmentioning
confidence: 76%
“…We observed that patients with influenza A (H1N1) were more likely to require ICU support than those with either influenza A (H3N2) or influenza B. [59][60][61] Therefore, it is plausible that influenza A (H1N1) may reflect more severe illness, which could partly explain the higher risk of IPA in this influenza subtype population. Considering the high probability of the development of IPA in influenza patients, primary prophylaxis may be considered in select populations with high-risk conditions.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, higher rates of ACS in our study are probably related to the differences in cardio vascular disease (CVD) risk factor profile because patients in our study were older (median age 82 years vs. 77 years in the US study). In addition, these differences in rates of ACS may be related to the virulence of circulating influenza strains in respective epidemiological season [23] . Another study [15] , which included 264 influenza patients admitted over a period of 5 years where hsTnT results were available, found that 31.8% of patients had elevated cardiac biomarkers and 7.6% of these patients developed ACS, however, patients in this study were much younger (68.7 vs. 82 years) as compared to our population.…”
Section: Discussionmentioning
confidence: 99%